Evaluation to the effect of B2O3–La2O3–SrO–Na2O–Al2O3 bonding agent on Ti6Al4V–porcelain bonding. (October 2016) - Zhao, C.Q.; Wu, S.Q.; Lu, Y.J.; Gan, Y.L.; Guo, S.; Lin, J.J.; Huang, T.T.; Lin, J.X.
Abstract: Low-fusing bonding agents have been widely applied in Ti–ceramics restorations. As an important category, borate bonding agents have great potentials in increasing Ti–porcelain bonding. The purpose of this study is to evaluate the effect of borate bonding agent with addition of Na2 O and Al2 O3 on Ti6Al4V–porcelain bonding. The thermal properties of borate bonding agent, such as glass transition temperature ( T g ) and crystallization peak temperature ( T p ), were investigated to establish the sintering process. And the coefficient of thermal expansion (CTE) was to evaluate the matching effect of porcelain to Ti6Al4V. The bond strength was analyzed by the three point bending test. The microscopic morphology of the borate bonding agent surface after sintering, the interface of Ti–borate bonding agent-porcelain, and the fracture mode after porcelains fracture, were studied to assess the influence of borate bonding agent on Ti6Al4V–ceramics. With the addition of Na2 O and Al2 O3, the porcelain residues were observed increased indication on the Ti6Al4V surface after porcelain fracture and the bond strength was acquired the maximum (49.45 MPa) in the bonding agent composition of 75.70B2 O3 –5.92La2 O3 –11.84SrO–4.67Na2 O–1.87Al2 O3 . Those results suggest that borate bonding agent is an effective way to improve the Ti6Al4V–ceramics bond strength. And the addition of Na2 O and Al2 O3 strengthen this effect.